2011
DOI: 10.1021/ja2064389
|View full text |Cite
|
Sign up to set email alerts
|

Iterative in Situ Click Chemistry Assembles a Branched Capture Agent and Allosteric Inhibitor for Akt1

Abstract: We describe the use of iterative in situ click chemistry to design an Akt-specific branched peptide triligand that is a drop-in replacement for monoclonal antibodies in multiple biochemical assays. Each peptide module in the branched structure makes unique contributions to affinity and/or specificity resulting in a 200 nM affinity ligand that efficiently immunoprecipitates Akt from cancer cell lysates and labels Akt in fixed cells. Our use of a small molecule to pre-inhibit Akt prior to screening resulted in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 44 publications
(71 reference statements)
1
56
0
Order By: Relevance
“…156 Measuring Akt1 kinase activity under varying substrate and triligand concentrations eliminated the possibility of a competitive mode of Akt1 inhibition by the triligand with respect to ATP and peptide substrates. 150 This confirmed that the triligand binds to a location away from the active site of the kinase and that inhibition occurs via an allosteric mechanism. Finally, the anchor, biligand, and triligand were tested for the ability to recognize Akt from the ovarian cancer cell line OVCAR3 in immunoprecipitation (IP) experiments.…”
Section: Iterative In Situ Click Chemistrymentioning
confidence: 59%
See 3 more Smart Citations
“…156 Measuring Akt1 kinase activity under varying substrate and triligand concentrations eliminated the possibility of a competitive mode of Akt1 inhibition by the triligand with respect to ATP and peptide substrates. 150 This confirmed that the triligand binds to a location away from the active site of the kinase and that inhibition occurs via an allosteric mechanism. Finally, the anchor, biligand, and triligand were tested for the ability to recognize Akt from the ovarian cancer cell line OVCAR3 in immunoprecipitation (IP) experiments.…”
Section: Iterative In Situ Click Chemistrymentioning
confidence: 59%
“…150 Akt1 kinase is responsible for signal transduction from the plasma membrane to downstream effector molecules that control cell growth, apoptosis, and translation. 151 To ensure the development of an allosteric site inhibitor, Millward et al carried out an initial screen against a large OBOC peptide library on a kinase preinhibited with an ATP-competitive inhibitor, Ac7.…”
Section: Iterative In Situ Click Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, peptides that are protected from degradation via cyclization or stapling have been shown to exhibit high potency and low toxicity, resulting in more promising candidates for drug administration than their linear counterparts [3][4][5][6][7]. A myriad of nonlinear peptides are found naturally in plants, fungi, and bacteria as well as synthetic ones produced in the laboratory [10][11][12][13][14][15][16][17][18]. Valinomycin, for example, is a cyclic dodecadepsipeptide produced by Streptomyces fulvissimus with potent antibacterial properties while also acting as a potassium-selective ionophore [19,20].…”
Section: Introductionmentioning
confidence: 99%